Cellular responses and microRNA profiling in bovine spermatozoa under heat shock. Issue 4 (20th September 2022) - da Silva, Daniela F; Rodrigues, Thaís A; da Silveira, Juliano C; Gonella-Diaza, Angela M; Binelli, Mario; Lopes, Juliana V; Moura, Marcelo T; Feitosa, Weber B; Paula-Lopes, Fabíola F
Abstract : In brief: Elevated temperatures disturbed sperm physiology. Bovine sperm cells exposed to heat shock led to diminished mitochondrial activity, fertilizing ability, increased oxidative stress and caspase activity concomitant with a delay in embryonic developmental kinetics and modulation of sperm-borne microRNAsmiRNAs. Abstract: Sperm function is susceptible to adverse environmental conditions. It has been demonstrated that in vivo and in vitro exposure of bovine sperm to elevated temperature reduces sperm motility and fertilizing potential. However, the cascade of functional, cellular, and molecular events triggered by elevated temperature in the mature sperm cell remains not fully understood. Therefore, the aim of this study was to determine the effect of heat shock on mature sperm cells. Frozen-thawed Holstein sperm were evaluated immediately after Percoll purification (0 h non-incubation control) or after incubation at 35, 38.5, and 41°C for 4 h. Heat shock reduced sperm motility after 3–4 h at 41°C while mitochondrial activity was reduced by 38.5 and 41°C when compared to the control. Heat shock also increased sperm reactive oxygen species production and caspase activity. Heat-shocked sperm had lower fertilizing ability, which led to diminished cleavage and blastocyst rates. Preimplantation embryo developmental kinetics was also slowed and reduced by sperm heat shock. The microRNA (miR) profiling identified >300 miRs in bovine sperm. Among these, three and seven miRs were exclusively identified in sperm cells exposed to 35 and 41°C, respectively. Moreover, miR-181d was enriched in sperm cells exposed to higher temperatures. Hence, elevated temperature altered the physiology of mature sperm cells by perturbing cellular processes and the miR profile, which collectively led to lower fertilizing ability and preimplantation development.